Novos parâmetros geométricos de componentes de tubos de vórtice para operação em baixas pressões e acionamento por sistema fotovoltaico - Clemente, Hugo Alberto López (2018)
The study of the cooling system with vortex tube enables the reduction of the impact of global warming generated by conventional refrigeration systems. In these systems, 20% are in direct emissions of refrigerants, and 80% in indirect emissions of greenhouse effect gases that are the result of the electricity production in thermal power plants. The vortex tube is cooling device with easy maintenance and low cost. It has applications in domestic and industrial sectors. A photovoltaic system can power the air compressor of the vortex tube for use in isolated areas, as well as connected directly to the grid in urban areas. This work investigates new geometric parameters for a vortex tube that operates in counter flow. These parameters are the lengthdiameter ratio (L/D), the inlet nozzle diameter, the injection mode in the vortex chamber, and the number of nozzles in the generator. The purpose is to produce cold air streams at pressures of 2, 3 and 4 bar, to facilitate its operation by a photovoltaic system. The chamber and vorticity generators were manufactured in a 3D printer with biodegradable plastic (lactic polyacid). The experimental results showed that the highest cold air temperature difference and the best coefficient of performance (COP) were obtained for a vortex tube with a ratio of L/D=40, a vortex generator with 1 nozzle, with tangential injection of the compressed air, and inlet nozzle diameters of 5.5 mm and 7 mm. According to cost surveys of the photovoltaic systems, the results show that the system connected to the grid presented a lower cost than the isolated system, but the latter could be indicated for places where the grid is not available.